ANALISIS NILAI GUNA HUTAN SEBAGAI PENYEDIAN AIR BERSIH DAN IMPLEMENTASI PES (Payment For Ecosystem Service) BAGI PEMILIK DUSUN DI HUTAN LINDUNG GUNUNG SIRIMAU KOTA AMBON - Joseph Latuihamallo; Jusmy D Putuhena (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
Upstream of the five watersheds in the city of Ambon has been designated as protected areas namely Hutan lindung Gunung Sirimau this area can support the function hidroorologis to regulate the water system and the provision of clean air for people in the city of Ambon, but in fact Kawasan Lindung Gunung Sirimau are a place of settlement for several villages. The purpose of this study is: Knowing the Land Use Activities and Agroforestry activities in the upstream watershed in Forest Protection Gunung Sirimau, Knowing the role of upstream watershed for suppling of Clean Water to the area downstream, Finding the service value of Hutan Lindung Gunung Sirimau, Making Implementation scheme of Payment For Ecosystem Service in Ambon.Hutan Lindung Gunung Sirimau have the economic value of water produced per hectare of forest Rp. 1,190,411, - / ha per year. PES schemes will be implemented in the upstream watershed in Ambon when there is engagement between the relevant agencies with 3 pillars ; (1) the government figure is represented by Raja; (2) a religious figure represented by Pastor / Ulama; (3) Teacher in the village.